Fricatives, affricates, and vowels in Croatian children with cochlear implants - Mildner, Vesna (Array, 2008)
The aim of the research was to analyze the speech of the children with cochlear implants over approximately a 46-month period, and compare it with the speech of hearing controls. We focused on three categories of sounds in Croatian: vowels (F1 and F2 of /i/, /e/, /a/, /o/ and /u/), fricatives /s/ and /∫ / (spectral differences expressed in terms of center of gravity), and affricates /ts/ and /t∫ / (accuracy, total duration and pattern of stop-fricative components). One group of subjects were 10 implanted children who had been profoundly deaf before implantation. There were four recordings per child. Group two were hearing controls matched for age and sex. The results show that the implanted children are closest to unimpaired children in terms of their formant-defined vowel space. Their fricatives exhibit poor distinction in terms of the noise spectrum, and the affricates are the most difficult to produce.